Pengaruh Harga Produk dan Layanan Terhadap Inflasi di Kabupaten Deli Serdang Menggunakan Metode Rancangan Acak Kelompok Lengkap (RAKL) - Achmad Fajri Romadhoni; Ayu Widya Sari; Ega Ananda br Sembiring; Ishak Munawar; Sudianto Manullang; Putri Maulidina Fadilah (Interdisciplinary Explorations in Research Journal, 2024)
This research explores the influence of product and service prices on the inflation rate in Deli Serdang Regency, using the Complete Randomized Block Design (RAKL) method. The data used includes the inflation rate of eight categories of goods and services reported by the Central Statistics Agency during the period January to June 2024. The results of variance analysis show that neither the goods/services category factor nor product prices have a significant influence on the inflation rate in the research period. This study provides initial insight into the relationship between prices and inflation and opens up opportunities for further research with broader data coverage and additional variables.